2018
DOI: 10.12659/msm.909719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kanglaite Injection on Serum miRNA-21 in Patients with Advanced Lung Cancer

Abstract: BackgroundLung cancer is the most common type of cancer throughout the world, and the morbidity of lung cancer is continuously increasing. Patients with advanced lung cancer often cannot tolerate chemoradiotherapy. The decrease of the expression of miRNA-21 can be used as an indicator of the therapeutic effect of lung cancer. In this study, the effect of Kanglaite injection on serum miRNA-21 in patients with advanced lung cancer was investigated, providing reliable and important evidences.Material/MethodsFrom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Kanglaite ® injection as a commercial formulation of coix seed oil has already been approved as a supplementary drug for chemotherapeutics in various anticancer treatments. 30,31 According to our previous reports, combinational therapy with coix seed oil and chemotherapeutics enhances anticancer efficacy through a collaborative mechanism. 32,33 Inspired by this strategy, we determined the possibility of synergistic antitumor effects after assembling tripterine and coix seed oil into a microemulsion system.…”
Section: Introductionmentioning
confidence: 99%
“…Kanglaite ® injection as a commercial formulation of coix seed oil has already been approved as a supplementary drug for chemotherapeutics in various anticancer treatments. 30,31 According to our previous reports, combinational therapy with coix seed oil and chemotherapeutics enhances anticancer efficacy through a collaborative mechanism. 32,33 Inspired by this strategy, we determined the possibility of synergistic antitumor effects after assembling tripterine and coix seed oil into a microemulsion system.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA plays a part in the regulation of physiological processes, such as cell biological development, lipid metabolism and hormone secretion, as well as the occurrence and development of diabetes, viral infection and tumor. 15 , 16 Studies have found that miRNAs are involved in the progression of tumors as oncogenes or tumor suppressor genes. 17 The miRNAs not only enriches the understanding of gene regulatory networks in theory, but also has great potential in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, KLTi inhibits tumor necrosis factor-alpha-(TNF-α-) mediated epithelial mesenchymal transition (EMT) in colorectal cancer cell lines by inhibiting the NF-κΒ signaling pathway [52]. According to research reports, clinical use of KLTi provides objective evidence for the treatment of lung cancer and significantly reduces the expression of miRNA-21 in patients with advanced lung cancer [53]. In this comprehensive systematic review and meta-analysis, we comprehensively evaluated whether KLTi combined with chemotherapy versus chemotherapy alone benefits patients with advanced NSCLC.…”
Section: Summary Of Evidencementioning
confidence: 99%